Ultralow-temperature vacuum lubricating coating and preparation method thereof
By using the composite technology of graphite-based materials with specific layered structures and low-temperature bonding agents, graphite-based composite coatings were prepared, and the graphite roller structure was induced by ultra-low temperature friction, which solved the poor tribological performance of lubricating materials under ultra-low temperature environments. The problem of low friction and wear performance has been achieved.
Patent Information
- Application Number
- CN202410711393.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-06-04
Smart Images

Figure CN119463686A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ultra-low temperature vacuum lubrication coating and a preparation method thereof, and belongs to the field of mechanical lubrication. Background Art
[0002] With the rapid development of my country's key development areas such as lunar exploration, deep space exploration, superconductivity and quantum computing, the lubrication of moving parts at ultra-low temperatures has become a technical problem, and the reliable service of materials in extreme ultra-low temperature environments has become the key to future frontier scientific and technological breakthroughs. For example, when the Chang'e 7 lunar rover performs the lunar polar exploration mission, it will face the requirement of long-term continuous operation at ultra-low temperatures below 100 K, while its existing mobile subsystem is mainly in a dormant state at low temperatures. At present, the material system of ultra-low temperature friction is mainly space lubrication materials such as polymers, metals, solid bonding coatings, and vacuum sputtering lubrication films. However, most materials face the deterioration of tribological properties at ultra-low temperatures. my country's targeted research on ultra-low temperature tribology is very scarce, and there is a gap in the field of lubrication technology at working temperatures below -65℃, which seriously restricts the selection of lubricating materials and equipment reliability assurance under ultra-low temperature service conditions. It is urgent to develop ultra-low temperature lubrication technology.
[0003] As an important solid lubricant, graphite has a typical layered structure with weak van der Waals forces between layers. It has excellent lubrication performance in air, but it is easy to fail in vacuum, which has caused major air crashes. However, the inventor of this patent discovered in previous studies that the lamellar graphite material self-curls to form a graphite roller structure during ultra-low temperature friction. This ultra-low temperature friction-induced graphite roller structure is used to achieve molecular rolling lubrication; based on this discovery, the present invention creatively introduces a graphite-based lubricant with a specific layered structure and compounds it with a low-temperature resistant binder to invent an ultra-low temperature (20-200K) vacuum (vacuum degree <5×10 -4 The composite coating technology with excellent lubrication and wear resistance in the environment of 200 Pa provides technical support for solving the low-temperature lubrication problems of low-temperature service equipment in aerospace, superconductivity, quantum computing, polar regions, etc. Summary of the invention
[0004] The object of the present invention is to provide a graphite-based composite coating with low friction and wear performance in an ultra-low temperature vacuum environment and a preparation method thereof.
[0005] 1. Preparation of graphite-based composite coating (1) Preparation of lubricant dispersion A graphite-based material with a lamellar structure is added to a dispersion at a mass concentration of 400-4000 mg / L. The number of layers of the graphite-based material with a lamellar structure is 1-100, and the lateral size of the lamellar layer is distributed in the range of 0-100 µm. Then ultrasonic dispersion is performed to obtain a lubricant dispersion. The graphite-based material can be graphite, microcrystalline graphite or graphene, and the dispersion can be deionized water, anhydrous ethanol, N,N-dimethylformamide or N,N-dimethylacetamide. The ultrasonic power ranges from 500-2000 W during ultrasonic dispersion, and the ultrasonic time is 10-150 min.
[0006] (2) Preparation of composite dispersion A low-temperature resistant binder is added to the dispersion in step (1), and the low-temperature resistant binder can be polyamide-imide, polyimide, polyetheretherketone, polyurethane or epoxy resin, and the mass ratio of the binder to the lubricant is in the range of 1:0.05-1:20, and the mass content of the solid component in the composite dispersion is 10%-50%. Then, ultrasonic dispersion is performed, and the ultrasonic power during ultrasonic dispersion is 500-2000 W, and the ultrasonic time is 5-120 min.
[0007] (3) Preparation of graphite-based composite coatings The composite dispersion prepared in step (2) is sprayed on the surface of the substrate under compressed air (oil-free) or compressed nitrogen. The substrate material is selected from metals such as bearing steel, stainless steel, aluminum or titanium alloy. The surface is dried in a drying cabinet or in the air, and then placed in a blower for curing. The curing procedure is to heat to 150-180°C within 40-120 minutes, keep warm for 60-180 minutes, then heat to 260-280°C within 40-120 minutes, keep warm for 60-120 minutes; finally, cool naturally to obtain a graphite-based composite coating.
[0008] The lubrication mechanism of the graphite-based composite coating of the present invention is as follows: Under a vacuum ultra-low temperature environment, due to the temperature difference between the upper and lower surfaces of the frictionally peeled graphite nanosheets, the edges of the sheets will experience a unique self-curling effect. Utilizing this effect, the friction shear force further drives the curled-up sheets to wrap around and form in situ a graphite scroll structure that is arranged in parallel along the friction sliding direction ( Figure 1 ), these molecular scrolls can play a role of rolling lubrication just like wheels. Therefore, the graphite-based composite coating of the present invention exhibits low friction and wear characteristics in a vacuum ultra-low temperature environment.
[0009] 2. Microstructure of friction interface of graphite-based composite coating Figure 1This is a high-resolution transmission electron microscope morphology of the special graphite roller structure formed on the friction interface of the graphite-based composite coating in the ultra-low temperature vacuum environment. It can be seen that the graphite-based material with a lamellar structure forms a graphite roller structure, and its axial length is hundreds of microns. This structure can play a rolling lubrication role at the friction interface, which plays a vital role in obtaining low friction and wear performance of the graphite-based composite coating in an ultra-low temperature vacuum environment.
[0010] 3. Tribological properties of graphite-based composite coatings The flat sample prepared by the present invention was used as the lower sample, and a commercial steel ball (Ø6 mm, GCr15, Ra≈20 nm) was used as the upper sample. -4 Pa, the temperature is within the full temperature range of 20~200K, and the normal load is 1-5N. The evaluation is carried out on a ball-disc friction tester using a unidirectional linear rotation mode. The rotation radius is 5~10mm and the rotation speed is 60~120rpm.
[0011] Figure 2 The graphite-based composite coating prepared by the present invention is shown in Fig. -4 Table 1 shows the friction coefficient variation curve in ultra-low temperature (20-200K) vacuum (vacuum degree <5×10 -4 The experimental results of friction coefficient and wear rate of graphite-based composite coatings in the environment of 20-200K show that the friction coefficient is maintained at 0.04-0.06 and the wear rate is 1.0×10 -8 ~1.0 ×10 -7 mm 3 / (N·m) order of magnitude.
[0012] Table 1 Experimental results of friction coefficient and wear rate of graphite-based composite coatings In summary, the present invention uses a graphite-based material with a special lamellar structure to prepare a graphite-based composite coating, and utilizes ultra-low temperature friction to induce the formation of a graphite roller structure to achieve molecular rolling lubrication, thereby obtaining low friction and wear performance in an ultra-low temperature vacuum environment. The present invention provides a new ultra-low temperature vacuum lubrication technology, and the graphite-based composite coating can be used for surface lubrication treatment of moving parts of low-temperature service equipment such as aerospace, superconductivity, quantum computing, and polar regions. At the same time, the preparation method of the coating in the present invention is simple and easy, and is suitable for promotion and application in engineering parts and operating conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a high-resolution transmission electron microscope photograph of a special graphite roller structure formed on the friction interface of the graphite-based composite coating of the present invention.
[0014] Figure 2 The graphite-based composite coating of the present invention is -4 Friction coefficient curve in the environment of Pa. DETAILED DESCRIPTION
[0015] The technical scheme of the present invention is further described in detail below in conjunction with several preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present invention. The specific conditions and test methods not clearly described in the following embodiments are usually based on conventional conditions.
[0016] Example 1 (1) Adding lamellar microcrystalline graphite at a mass concentration of 600 mg / L into a deionized water dispersion, wherein the number of layers of the microcrystalline graphite is about 60 and the lateral size of the lamellar layer is about 10 µm. Then ultrasonic dispersion is performed, the ultrasonic time is 20 min, and the ultrasonic power is 500 W to obtain a deionized water dispersion of microcrystalline graphite.
[0017] (2) Adding polyimide resin to the microcrystalline graphite deionized water dispersion obtained in step (1), wherein the mass ratio of polyimide to microcrystalline graphite is 1:1, and the mass content of the solid component in the composite dispersion is 25%. Then, ultrasonic dispersion is performed, the ultrasonic time is 120 minutes, and the ultrasonic power is 500W.
[0018] (3) The composite dispersion prepared in step (2) is sprayed on the surface of the stainless steel substrate under compressed nitrogen, dried in the air, and then placed in a blower for curing. The curing procedure is to heat to 160° C. within 60 minutes, keep warm for 60 minutes, then heat to 260° C. within 60 minutes, keep warm for 120 minutes, and then cool naturally to obtain a microcrystalline graphite composite coating.
[0019] Tribological performance test: The friction coefficient was evaluated on a ball-disc friction tester, with the flat sample prepared in this embodiment as the lower sample and a commercial steel ball (Ø6 mm, GCr15, Ra ≈ 15 nm) as the upper sample, in a vacuum of 3.0×10 -5 Pa, the temperature is 20K, the normal load is 1N, and the unidirectional linear rotation mode is used for evaluation on the ball-disc friction tester. The results are shown in Table 1. During the experiment, the rotation radius is kept at 5mm and the rotation speed is kept at 120rpm.
[0020] Example 2 (1) Add lamellar graphite at a mass concentration of 1000 mg / L into a dispersion of N,N-dimethylacetamide, wherein the number of graphite layers is about 100 and the lateral size of the lamellar layer is about 15 µm. Then ultrasonic dispersion is performed, the ultrasonic time is 40 min, and the ultrasonic power is 1000 W to obtain a dispersion of graphite in N,N-dimethylacetamide.
[0021] (2) Adding polyamide-imide resin to the graphite N,N-dimethylacetamide dispersion obtained in step (1), wherein the mass ratio of polyamide-imide resin to graphite is 2:1, and the mass content of solid components in the composite dispersion is about 15%. Then, ultrasonic dispersion is performed, and the ultrasonic time is 60 min and the ultrasonic power is 500 W.
[0022] (3) The composite dispersion prepared in step (2) is sprayed on the surface of an M2 high-speed steel substrate under compressed air (oil-free), dried in the air, and then placed in a blower for curing. The curing procedure is to heat to 180°C within 120 minutes, keep the temperature for 120 minutes, then heat to 280°C within 120 minutes, keep the temperature for 60 minutes, and then cool naturally to obtain a graphite composite coating.
[0023] Tribological performance test: The friction coefficient was evaluated on a ball-disc friction tester, with the flat sample prepared in this embodiment as the lower sample and commercial alumina (Ø6 mm, Al2O3, Ra ≈ 10 nm) as the upper sample, in a vacuum of 4.0×10 -4 When the friction coefficient was 0.0447 W / m, the temperature was 80 K, and the normal load was 1 N, the test was carried out on a ball-disc friction tester in a unidirectional linear rotation mode, and the results are shown in Table 1. During the experiment, the rotation radius was kept at 10 mm and the rotation speed was kept at 60 rpm.
[0024] Example 3 (1) Adding lamellar graphene at a mass concentration of 800 mg / L into a N,N-dimethylformamide dispersion, wherein the number of graphene layers is 8-10 and the lateral size of the lamellar layer is about 0.5-5 µm. Then ultrasonic dispersion is performed, the ultrasonic time is 60 min, and the ultrasonic power is 1000 W to obtain a graphene N,N-dimethylformamide dispersion.
[0025] (2) Add epoxy resin to the graphene N,N-dimethylformamide dispersion obtained in step (1). The mass ratio of epoxy resin to graphene is 1:4, and the mass content of solid components in the composite dispersion is 30%. Then, ultrasonic dispersion is performed, and the ultrasonic time is 40 min and the ultrasonic power is 1000 W.
[0026] (3) Spraying the composite dispersion prepared in step (2) onto the surface of the titanium alloy substrate under compressed nitrogen, drying the surface in a drying cabinet, and then curing in a blower. The curing procedure is to heat to 170° C. within 80 min, keep the temperature for 180 min, then heat to 270° C. within 80 min, keep the temperature for 120 min, and then cool naturally to obtain a graphene composite coating.
[0027] Tribological performance test: The friction coefficient was evaluated on a ball-disc friction tester, with the flat sample prepared in this embodiment as the lower sample and commercial silicon nitride (Ø6 mm, Si3N4, Ra ≈ 10 nm) as the upper sample, in a vacuum of 4.0×10 -4 When the friction coefficient was 0.0447 W / m, the temperature was 160 K, and the normal load was 2 N, the test was carried out on a ball-disc friction tester in a unidirectional linear rotation mode, and the results are shown in Table 1. During the experiment, the rotation radius was kept at 10 mm and the rotation speed was kept at 60 rpm.
[0028] Example 4 (1) Adding lamellar graphite at a mass concentration of 800 mg / L into an anhydrous ethanol dispersion, wherein the number of graphene layers is 100 and the lateral size of the lamellar layer is about 40 µm. Then ultrasonic dispersion is performed, the ultrasonic time is 120 min, and the ultrasonic power is 2000 W to obtain an anhydrous ethanol dispersion of graphite.
[0029] (2) Adding polyurethane resin to the graphite anhydrous ethanol dispersion obtained in step (1), wherein the mass ratio of polyurethane resin to graphite is 1:0.5, and the mass content of solid components in the composite dispersion is 40%. Then, ultrasonic dispersion is performed, the ultrasonic time is 60 min, and the ultrasonic power is 1500 W.
[0030] (3) Spraying the composite dispersion prepared in step (2) onto the surface of an aluminum alloy substrate under compressed nitrogen, drying the surface in a drying cabinet, and then curing in a blower. The curing procedure is to heat the dispersion to 160° C. within 60 min, keep the temperature for 120 min, then heat the dispersion to 260° C. within 80 min, keep the temperature for 100 min, and then cool the dispersion naturally to obtain a graphite composite coating.
[0031] Tribological performance test: The friction coefficient was evaluated on a ball-disc friction tester, with the flat sample prepared in this embodiment as the lower sample and commercial tungsten carbide (Ø6 mm, WC, Ra ≈ 10 nm) as the upper sample. -5Pa, the temperature was 200 K, and the normal load was 5 N. The unidirectional linear rotation mode was used to evaluate the friction test on the ball-disc tester, and the results are shown in Table 1. During the experiment, the rotation radius was kept at 10 mm and the rotation speed was kept at 100 rpm.
Claims
1. A method for preparing an ultra-low temperature vacuum lubricating coating, characterized in that: The following steps are involved: 1) Preparation of lubricant dispersion: adding a graphite-based material with a lamellar structure into a dispersion at a mass concentration of 400-4000 mg / L, and then uniformly dispersing by ultrasonication to obtain a lubricant dispersion; 2) Preparation of composite dispersion: adding a low-temperature resistant binder to the lubricant dispersion obtained in step 1), and obtaining a composite dispersion after ultrasonic dispersion; 3) Preparation of graphite-based composite coating: spray the composite dispersion prepared in step 2) on the surface of the substrate under compressed air or compressed nitrogen, place it in a drying cabinet or in the air to dry, and then put it into a blower for curing. The curing procedure is to first heat it to 150-180°C within 40-120 minutes, keep it warm for 60-180 minutes, then heat it to 260-280°C within 40-120 minutes, keep it warm for 60-120 minutes, and finally cool it naturally to obtain a graphite-based composite coating.
2. The method for preparing an ultra-low temperature vacuum lubricating coating according to claim 1, characterized in that: In step 1), the number of layers of the graphite-based material in the lamellar structure is 1 to 100, and the lateral size of the lamellar structure is distributed in the range of 0 to 100 µm.
3. The method for preparing an ultra-low temperature vacuum lubricating coating according to claim 2, characterized in that: In step 1), the graphite-based material is at least one of graphite, microcrystalline graphite or graphene.
4. The method for preparing an ultra-low temperature vacuum lubricating coating according to claim 1, characterized in that: In step 1), the dispersion liquid is at least one of deionized water, anhydrous ethanol, N,N-dimethylformamide, and N,N-dimethylacetamide.
5. The method for preparing an ultra-low temperature vacuum lubricating coating according to claim 1, characterized in that: In step 2), the binder is at least one of polyamide-imide, polyimide, polyetheretherketone, polyurethane and epoxy resin, and the mass ratio of the binder to the lubricant is 1:0.05-1:20, and the overall solid content in the composite dispersion is 10%-50%.
6. The method for preparing an ultra-low temperature vacuum lubricating coating according to claim 1, characterized in that: In step 3), the substrate is one of bearing steel, stainless steel, aluminum or titanium alloy.
7. An ultra-low temperature vacuum lubricating coating prepared by the method as claimed in claim 1.
8. An application of the ultra-low temperature vacuum lubricating coating prepared by the method as claimed in claim 1 for lubricating the surface of moving parts of low temperature service equipment.
Citation Information
Patent Citations
Room temperature-curing high vacuum and ultralow temperature resistant lubrication coating
CN103834284A
Self-lubricating composite material preparation method and self-lubricating composite material
CN105797940A
Composite super-lubricating coating with nanometer curling structure and preparation method thereof
CN112574800A
LUBRICANT COMPOSITION AND METHOD OF ITS PREPARATION
RU2014104202A
Lubrication material using self-dispersed crumpled graphene balls as additives in oil for friction and wear reduction
US20170088788A1